Social Protection in Health: Characteristics and Coverage of Health Insurance Programme in Nepal - Khanal, Geha Nath; Regmi, Bhagawan (Journal of Social Protection, 2020)
The agenda of social protection has become very popular in recent years. Several social protection programs in healthcare are designed to increase the healthcare coverage, ensure financial protection and enhance the scope and quality of services and access to medicines which ultimately paves the way for universal health coverage. The national health insurance programme (NHIP) is one of the approaches implemented in Nepal to cover healthcare expenditure. This paper discusses the gradual development of the health insurance programme in Nepal and the key features of NHIP that have been implemented since 2016. It further highlights the implementation status of NHIP, the milestones it covered, and the role of political parties in implementing NHIP in Nepal. Furthermore, the paper discusses the challenges associated with enrollment of formal and non-formal sectors, the mismatch between geographical coverage and the number of service contact points, and commitment from the political parties for effective implementation of NHIP. It seeks major implementation reforms to ensure effective implementation of NHIP.